2019
DOI: 10.3390/ijms20215323
|View full text |Cite
|
Sign up to set email alerts
|

Single-Channel Properties of the ROMK-Pore-Forming Subunit of the Mitochondrial ATP-Sensitive Potassium Channel

Abstract: An increased flux of potassium ions into the mitochondrial matrix through the ATP-sensitive potassium channel (mitoKATP) has been shown to provide protection against ischemia-reperfusion injury. Recently, it was proposed that the mitochondrial-targeted isoform of the renal outer medullary potassium channel (ROMK) protein creates a pore-forming subunit of mitoKATP in heart mitochondria. Our research focuses on the properties of mitoKATP from heart-derived H9c2 cells. For the first time, we detected single-chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 69 publications
2
42
0
Order By: Relevance
“…As it was reported in earlier studies, in the heart, Kir6.2 was dispensable for the K + conductance stimulated by diazoxide [31]. Also, none of ROMK isoforms (Kir1.1, Kir3.1, and Kir3.4) proposed as K + conductant subunit of mK ATP -channel [33,34] was responsible for diazoxide-induced swelling of cardiac mitochondria [32]. These studies indicated that K + conductant subunit of mK ATP -channel didn't belong to either Kir6.x, or Kir1.x channels, but molecular nature of the K + pore of mK ATP -channel remained elusive.…”
Section: Side Effect Of Diazoxide On Potassium Uptake In Rat Liver MIsupporting
confidence: 58%
“…As it was reported in earlier studies, in the heart, Kir6.2 was dispensable for the K + conductance stimulated by diazoxide [31]. Also, none of ROMK isoforms (Kir1.1, Kir3.1, and Kir3.4) proposed as K + conductant subunit of mK ATP -channel [33,34] was responsible for diazoxide-induced swelling of cardiac mitochondria [32]. These studies indicated that K + conductant subunit of mK ATP -channel didn't belong to either Kir6.x, or Kir1.x channels, but molecular nature of the K + pore of mK ATP -channel remained elusive.…”
Section: Side Effect Of Diazoxide On Potassium Uptake In Rat Liver MIsupporting
confidence: 58%
“…ROMK proteins are encoded by distinct splice variants of the Kcnj1 gene. The expression of ROMK in mitochondria and patch-clamp measurements confirmed its functional properties as a mitoK ATP channel [27]. Recently, it was proposed that the CCDC61 and ABCB8 proteins constitute a mitoK ATP channel composed of pore-forming and ATP-binding subunits (mitochondrial sulfonylurea receptor) [29].…”
Section: Plasma Membrane Versus Mitochondrial Potassium Channels: Molmentioning
confidence: 77%
“…The current (June 2020) list of identified mitochondrial potassium channels is as follows: mitoK ATP channel: mitochondrial ATP-regulated potassium channel, the first potassium channel described in the inner mitochondrial membrane [ 1 ]. Most likely, these channels might be formed by two proteins: ROMK-type channels (encoded by KCNJ1 gene) [ 25 , 26 , 27 , 28 ] or the recently described CCDC51 protein (encoded by CCDC51 gene) [ 29 ]. Additionally, ABCB8 protein (mitochondrial sulfonylurea receptor) is part of the mitoK ATP channel [ 29 ].…”
Section: Three-dimensional Mitochondrial Potassium Channel Mappingmentioning
confidence: 99%
“…Moreover, carbacetam is not excluded to modulate Ca 2+ and K + currents. Activation of mitochondrial ATP-dependent potassium channels is known to result in the decrease of Ca 2+ load and inhibition of an excessive opening of the mitochondrial pore 16,17 .…”
Section: Resultsmentioning
confidence: 99%